Endovascular Management of Iatrogenic Pseudoaneurysm of Internal Maxillary Artery after Dental Extraction - Harsh Anand Singh; Ishan Kumar; Pramod Kumar Singh; Anshul Varshney; Ashish Verma (Journal of Clinical Interventional Radiology ISVIR)
Pseudoaneurysm developing from the internal maxillary artery is a rare but potentially fatal condition. We describe a case of iatrogenic pseudoaneurysm of the internal maxillary artery developed during dental extraction and successful endovascular closure of the feeder artery. At 2-month follow-up, the patient remained well with persistent thrombosis of pseudoaneurysm.